La literatura como Herramienta Didáctica para la Enseñanza de la Historia de la Violencia en Colombia - Romero Botero, Angie Daniela (Universidad Antonio Nariño, 2022)
This research is developed as a compilation monograph, in which literature is approached as a tool for the teaching of violence in Colombia, in order to seek new teaching practices to be able to address these topics of interest and to generate in students critical thinking and understand how these events that, although they are part of the country's history, continue to affect today